2012
DOI: 10.1523/jneurosci.4008-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor 2 Signaling in Peripheral Immune Cells Modulates Disease Onset and Severity in Mouse Models of Huntington's Disease

Abstract: Peripheral immune cells and brain microglia exhibit an activated phenotype in premanifest Huntington’s disease (HD) patients that persists chronically and correlates with clinical measures of neurodegeneration. However, whether activation of the immune system contributes to neurodegeneration in HD, or is a consequence thereof, remains unclear. Signaling through cannabinoid receptor 2 (CB2) dampens immune activation. Here, we show that the genetic deletion of CB2 receptors in a slowly progressing HD mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 58 publications
3
82
0
Order By: Relevance
“…Genetic deletion of cannabinoid receptor 2 (CB2) -a protein expressed predominantly in peripheral immune cells that regulates production of proinflammatory cytokines, likely via NF-κB (65-67) -exacerbates pathogenesis in a mouse model of HD (68). Consistent with these findings, we recently found that CB2 signaling in immune cells mediates the onset and severity of symptoms in BACHD mice and that CB2 agonists are neuroprotective in R6/2 mice, even when given at late disease stages (69). Finally, inhibition of kynurenine 3-monooxygenase (KMO) in blood cells prevented synaptic loss and brain inflammation and increased lifespan in R6/2 mice (56).…”
Section: Figurementioning
confidence: 68%
“…Genetic deletion of cannabinoid receptor 2 (CB2) -a protein expressed predominantly in peripheral immune cells that regulates production of proinflammatory cytokines, likely via NF-κB (65-67) -exacerbates pathogenesis in a mouse model of HD (68). Consistent with these findings, we recently found that CB2 signaling in immune cells mediates the onset and severity of symptoms in BACHD mice and that CB2 agonists are neuroprotective in R6/2 mice, even when given at late disease stages (69). Finally, inhibition of kynurenine 3-monooxygenase (KMO) in blood cells prevented synaptic loss and brain inflammation and increased lifespan in R6/2 mice (56).…”
Section: Figurementioning
confidence: 68%
“…However, as recent study unequivocally demonstrated that CB 1 R-dependent neuroprotective activity in HD is predominantly derived from a restricted population of these receptors on cortical glutamatergic neurons that project to the striatum and that are preserved during the progression of HD rather than from the CB 1 R located on striatal projection γ-aminobutyric acid (GABA)-ergic neurons that are progressively lost during disease progression [142], supporting the relevance of these receptors as potential targets for a neuroprotective therapy with cannabinoids in HD. In addition, the benefits found after CB 2 R activation in HD may be facilitated by overexpression of these receptors in the striatal parenchyma, an effect that was first detected when striatal damage was provoked in rats with malonate [134], and in R6/2 mice and other genetic mouse models of HD [135,143], as well as in postmortem tissues from patients with HD [134]. This upregulation appears to occur in astrocytes [134] (although no CB 2 R expression was found in these glial cells in human HD tissues [144]) and particularly in reactive microglia [134,135].…”
Section: Cannabinoids and Chronic Neurodegenerative Disorders: III Hdmentioning
confidence: 99%
“…Inflammatory reactions, specifically microglial activation and/or cytokine release, have been described in brains of HD patients (Sapp et al, 2001;Pavese et al, 2006;Silvestroni et al, 2009) and mouse models (Bjorkqvist et al, 2008;Bouchard et al, 2012;Kwan et al, 2012), including R6/2 mice Wacker et al, 2009), and may contribute importantly to the progression of the disease (Möller, 2010). We evaluated the effect of LM22A-4 on inflammation, as assessed with immunostaining for IBA-1, a protein expressed by activated or proliferating microglia (Ridley et al, 1992;Imai et al, 1996;Ito et al, 1998), that is increased in R6/2 brains Wacker et al, 2009).…”
Section: Lm22a-4 Decreases Inflammation In the Striatum Of R6/2 Micementioning
confidence: 99%